1986
DOI: 10.1128/jcm.24.4.522-526.1986
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibodies and antigens of human parvovirus B19 by enzyme-linked immunosorbent assay

Abstract: Acute-phase serum from a patient with aplastic crisis provided sufficient human parvovirus B19 to make a monoclonal antibody against B19 and to develop antigen and immunoglobulin M (IgM) and IgG antibody detection enzyme-linked immunosorbent assays (ELISAs). The indirect capture antibody method was used for all three assays. Antigen was detected in 8 of 29 sera drawn within 2 days of onset of illness from patients with aplastic crisis. These sera had high titers of virus by electron microscopy and DNA hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
8

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(102 citation statements)
references
References 33 publications
5
89
0
8
Order By: Relevance
“…The overall seroprevalence rate and the age group-specific rate of anti-B19 antibody titers are shown in Table 3. These rates are consistent with previously reported data (4,14,22,25,46), indicating that the VP1 protein of B19 was properly prepared. The existence of HBoV IFA-positive and B19 IFA-negative or HBoV IFAnegative and B19 IFA-positive serum samples indicates that the anti-HBoV and anti-B19 sera did not cross-react with each other ( Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…The overall seroprevalence rate and the age group-specific rate of anti-B19 antibody titers are shown in Table 3. These rates are consistent with previously reported data (4,14,22,25,46), indicating that the VP1 protein of B19 was properly prepared. The existence of HBoV IFA-positive and B19 IFA-negative or HBoV IFAnegative and B19 IFA-positive serum samples indicates that the anti-HBoV and anti-B19 sera did not cross-react with each other ( Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…This epidemiological pattern may result from a combination of factors that facilitate B19V transmission, such as presence of highly viremic patients, nosocomial spread, transfusion-related transmission, and absence of well-defined diagnostic and therapeutic procedures [Regaya et al, 2007]. In the examined Brazilian region, the overall B19V seroprevalence was similar to that reported in the USA [Anderson et al, 1986], and Japan [Shiraishi et al, 1985], and significantly higher than that of some South eastern Asian countries (Hong Kong, Singapore, Taiwan) [Lim et al, 1997].…”
Section: Discussionmentioning
confidence: 69%
“…The aa 550-580 are shown with mutations of P558S and Y573G. results showed that the overall B19V IgG antibody presence is between 21.9% and 41.8% in various populations in the greater metropolitan area of Hangzhou, East China, which is lower than the rate ($60%) reported in adults worldwide [Nunoue et al, 1985;Anderson et al, 1986;Cohen and Buckley, 1988;Lim et al, 1997;Lin et al, 1999]. This result indicates that a large percentage of the population ($60%) in this area has not been exposed to B19V, and thus individuals living in this area might be at a high risk of becoming infected with B19V.…”
Section: Discussionmentioning
confidence: 86%
“…Since the first discovery of B19V in 1974 [Heegaard and Brown, 2002], B19V infection has been reported worldwide [McOmish et al, 1993;Jordan et al, 1998;Aubin et al, 2000;Heegaard et al, 2001;Thomas et al, 2003]. The presence of B19V antibody ranges from $20% in young children to $80% in people >60 years [Nunoue et al, 1985;Anderson et al, 1986;Cohen and Buckley, 1988;Lim et al, 1997;Lin et al, 1999]. The presence of B19V DNA in healthy blood donors could be as high as 1% [Azzi et al, 1999].…”
Section: Introductionmentioning
confidence: 99%